Regression of Breast Cancer Metastases Following Treatment with Irradiated SV-BR-1-GM, a GM-CSF Overexpressing Breast Cancer Cell Line: Intellectual Property and Immune Markers of Response - Wiseman, Charles L.; Kharazi, Alexander; Sunkari, Vivekananda G.; Galeas, Jacqueline L.; Dozio, Vito; Hashwah, Hind; Macúchová, Eva; Williams, William V.; Lacher, Markus D. (Recent Patents on Anti-Cancer Drug Discovery, 2023)
Background: SV-BR-1-GM, derived from a patient with grade 2 (moderately differentiated) breast cancer, is a GM-CSF-secreting breast cancer cell line with properties of antigen-presenting cells. SV-BR-1-GM and next-generation versions are covered by several pending and granted patents. Methods: We report findings from an open-label phase I, single-arm pilot study with irradiated SV-BR-1-GM cells in 3 breast and 1 ovarian cancer subjects. Inoculations were preceded by lowdose intravenous cyclophosphamide and followed by interferon-alpha2b injections into the SVBR- 1-GM inoculation sites. We assessed both cellular and humoral immune responses, and measured expression levels of SV-BR-1-GM HLA alleles. Results: Treatment was generally safe and well tolerated. Immune responses were elicited universally. Overall survival was more than 33 months for three of the four patients. As previously reported, one patient had prompt regression of metastases in lung, breast, and soft tissue. Following cessation of treatment, the patient relapsed widely, including in the brain. Upon retreatment, rapid tumor response was again seen, including complete regression of brain metastases. Consistent with a role of Class II HLA in contributing to SV-BR-1-GM’s mechanism of action, this patient allele-matched SV-BR-1-GM at the HLA-DRB1 and HLA-DRB3 loci. We are in the process of developing next-generation SV-BR-1-GM, expressing patient-specific HLAs. Patent applications were filed in various jurisdictions. Thus far, one is granted, in Japan. Conclusion: A whole-cell immunotherapy regimen with SV-BR-1-GM cells induced regression of metastatic breast cancer. We develop intellectual property based on SV-BR-1-GM’s predicted mechanism of action to develop additional whole-cell immunotherapies for cancer patients.
Keywords: whole-cell immunotherapy